The Effect of Liquidity Capital Structure, Company Size, Debt Policy and Profitability on Company Value in Property, Real Estate and Building Construction Companies Listed on the Indonesia Stock Exchange for the 2016-2019 Period - Cindy Fancella; Jholant Bringg Luck Amelia; Albert Chandra; sulina (Institute of Computer Science (IOCS), 2021)
Property, real estate and building construction in the past three years have faced a sluggish market. His research aims to determine the effect of capital structure, liquidity, company size, debt policy and profitability on firm value in property, real estate and building construction companies listed on the Indonesia Stock Exchange for the 2016-2019 period. The approach is quantitative with its kind of descriptive quantitative and causal nature. The population is 83 property, real estate and building construction with a sample of 23 companies. The result is that the capital structure does not have a partial effect on company value in property, real estate and building construction companies listed on the Indonesia Stock Exchange for the 2016-2019 Period. Liquidity does not have a partial effect on company value in property, real estate and building construction companies listed on the Indonesia Stock Exchange for the 2016-2019 period. The size of the company does not have a partial effect on the value of the company in the property, real estate and building construction companies listed on the Indonesia Stock Exchange for the 2016-2019 period. The debt policy does not have a partial effect on company value in property, real estate and building construction companies listed on the Indonesia Stock Exchange for the 2016-2019 period. Profitability has a partial effect on company value in property, real estate and building construction companies listed on the Indonesia Stock Exchange for the 2016-2019 period. Capital structure, liquidity, company size.